2018
DOI: 10.1111/imm.12988
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 contributes to disease severity in Dengue virus infection in mice

Abstract: The excessive inflammation often present in patients with severe dengue infection is considered both a hallmark of disease and a target for potential treatments. Interleukin-33 (IL-33) is a pleiotropic cytokine with pro-inflammatory effects whose role in dengue has not been fully elucidated. We demonstrate that IL-33 plays a disease-exacerbating role during experimental dengue infection in immunocompetent mice. Mice infected with dengue virus serotype 2 (DENV2) produced high levels of IL-33. DENV2-infected mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…In our study, dengue confirmed cases were outpatients with mild disease. In contrast, the majority of the other studies were conducted on hospitalized patients, which usually manifest greater disease severity and duration, consequently influencing the intensity of inflammatory and immune response [2224]. Yet, a previous evaluation of this RDT in Cambodia, enrolling children hospitalized due to a febrile illness of no clear source, showed an overall low sensitivity (57.8%) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dengue confirmed cases were outpatients with mild disease. In contrast, the majority of the other studies were conducted on hospitalized patients, which usually manifest greater disease severity and duration, consequently influencing the intensity of inflammatory and immune response [2224]. Yet, a previous evaluation of this RDT in Cambodia, enrolling children hospitalized due to a febrile illness of no clear source, showed an overall low sensitivity (57.8%) [21].…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 is centrally important in dengue virus infection and is strongly upregulated in mice that develop disease. The addition of recombinant exogenous IL-33 in dengue virus-infected mice resulted in severe disease with proinflammatory cytokine production and liver damage; thus, neutralization of IL-33 has been proposed as a target for therapeutics (36). The release of IL-33 is also important for responses to malaria and hepatotropic viruses, where high levels of IL-33 correlate with hepatic damage in humans (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vascular leakage is not observed in these DENV-infected immunocompetent mice. Although one group has reported a model of severe systemic disease in wild-type mice after infection with mouse-adapted DENV-2 and DENV-3 strains and used it to define mechanisms of immune control [29][30][31][32], these results have not been confirmed by independent groups. Thus, the utility of immunocompetent mice for studying DENV infection, pathogenesis, and disease remains limited.…”
Section: Mouse Models Of Dengue Infection and Pathogenesismentioning
confidence: 99%